PROSEDUR USULAN DAN PELAKSANAAN DIKLAT PADA PEMERIKSA DI BPK RI PERWAKILAN SUMATERA SELATAN - Niken Ayuningrum; Dimas Pratama Putra; Meta Agustariani (Jurnal RATRI (Riset Akuntansi Tridinanti), 2019)
ABSTRACTTraining is process or activity undertaken too broaden and to achieve certain goals that are beneficial for now or in the future. Implementation of training or education or training made by PUSDIKLAT and knowledge and skills of BPK examiners.The Study focuses on the proposed procedures and implementation of training in the implementation the preparation of the training procedure is required. The goal for the implementation of the training is more effective and implemented in accordance with the desired objectives. Another goal is the to provide information in the preparation of proposal and the implementation of training procedures in BPK RI representative of South Sumatra.Finally, this study provides information about the process are well as the proposal and implementation of training procedures in BPK or any other parties as a means of understanding the processes for the implementation of good training.Keywords: Training, Implementation Procedures, Means Understanding, Preparation Procedures Trainning.